SPECT/CT With the PSMA Ligand 99mTc-MIP-1404 for Whole-Body Primary Staging of Patients With Prostate Cancer. (April 2018) - Schmidkonz, Christian; Cordes, Michael; Beck, Michael; Goetz, Theresa Ida; Schmidt, Daniela; Prante, Olaf; Bäuerle, Tobias; Uder, Michael; Wullich, Bernd; Goebell, Peter; Kuwert, Torsten; Ritt, Philipp
Abstract : Background: 99m Tc-MIP-1404 (Progenics Pharmaceuticals, Inc, New York, NY) is a novel ligand binding to prostate-specific membrane antigen suitable for SPECT. There are, as yet, no data concerning its use in whole-body primary staging and its interobserver variability in patients with prostate cancer (PC) prior to therapy. Methods: A search of our clinical database from April 2013 to May 2017 yielded 93 patients with histologically confirmed cancer in whom 99m Tc-MIP-1404 SPECT/CT had been performed for primary whole-body staging before therapy. Whole-body planar and SPECT/CT images of the lower abdomen and thorax had been obtained 3 to 4 hours postinjection of 706 ± 72 MBq 99m Tc-MIP-1404. Images were visually analyzed for extent and location of abnormal uptake by 2 experienced nuclear physicians. Interobserver agreement for detection of primary tumor and metastatic lesions was assessed. In addition, SUVs of prostate-specific membrane antigen–positive regions of the prostate were determined in all patients, and from these, a variable reflecting total tumor load in the prostate gland was calculated (TUprostate ). Follow-up reports of subsequent therapeutic interventions were available in 52 (56%) of all patients with a median follow-up of 18 months. Results: In 90 (97%) of 93 patients, prostate uptake above background was detected as correlate of the histologically diagnosed PC. Forty-eight lymph node and 29 bone metastases were detected in 16 and 9 patients, respectively. In addition, 3 patients had disseminated bone metastases. No distant organ metastases were found. Interobserver agreement was high for the overall scan result (97%), as well as for the detection of the primary tumor (97%), of lymph node metastases (97%), and of bone metastases (99%). Recurrence of PC occurred in 5 patients in whom follow-up was available (10%). TUprostate was significantly higher in patients with Gleason scores of 8 or greater compared with patients with Gleason scores of 7 or less and at prostate-specific antigen (PSA) serum levels of 10 ng/mL or greater compared with PSA serum levels of 10 ng/mL or less. TUprostate of greater than 26 in the primary tumor predicted the occurrence of lymph node or bone metastases with a sensitivity of 82% and specificity of 76%. Conclusions: MIP-1404 SPECT/CT has a high accuracy and low interobserver variability in the diagnosis of PC and allows detection of lymph node and bone metastases in a significant proportion of as yet untreated PC patients. TUprostate is correlated with Gleason score and PSA serum concentration and allows prediction of the occurrence of lymph node and bone metastases with moderate accuracy at primary staging.